The Basic Theory of Corporate Governance in Islamic Perspective - Ince Nopica; Sanep Ahmad; Abdul Ghafar Ismail; Mohamat Sabri Hassan (Sharia and Law Faculty, 2017)
Recent studies that discuss governance in Islamic perspective have been done by various Islamic researcher including Abu-Tapanjeh (2008), Hassan (2009), Haweez (2013), etc. Most this research used the theoretical approach given in conventional corporate governance and provide additional Tahwid concept. The studies in-depth explanation of relationships between governance and Sharia principles (Islamic Law) is very limited therefore this paper tries to discuss and establish the basic theory of corporate governance based on Islamic Law. The approach used in this paper is the concept of human accountability (Amanah) on the mandate given by Allah SWT as Khalifatullah Fill Ardh. This paper expected can explore new approach to explain corporate governance in Islamic perspective.